2022
DOI: 10.1002/ccd.30227
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital mortality and readmission after ST‐elevation myocardial infarction in nonagenarians: A nationwide analysis from the United States

Abstract: Objectives To assess readmission rates in nonagenarians (age ≥ 90 years) with ST‐elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (pPCI) versus no pPCI. Background There are limited data exploring readmissions following STEMI in nonagenarians undergoing pPCI versus no pPCI. Methods We retrospectively analyzed the Nationwide Readmissions Database to identify nonagenarians hospitalized with STEMI. We divided the cohort into two groups based on pPCI status. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…However, the pro portion is still significantly lower when compared with younger adults in Poland [3]. A national analysis in the United States concluded that PCI is related to better sur vival of acute MI patients over 90 years of age [7]. Similar conclusions could be drawn based on analyses from other countries [8][9][10].…”
Section: Resultsmentioning
confidence: 75%
“…However, the pro portion is still significantly lower when compared with younger adults in Poland [3]. A national analysis in the United States concluded that PCI is related to better sur vival of acute MI patients over 90 years of age [7]. Similar conclusions could be drawn based on analyses from other countries [8][9][10].…”
Section: Resultsmentioning
confidence: 75%
“…In the cohort of patients aged >90 years, there were worse door-to-balloon times, and they had more complex lesion morphology, with more LMCA involvement (p < 0.001). However, cardiogenic shock and in-hospital mortality did not differ, highlighting the importance of pPCI in this subgroup (18).…”
Section: Discussionmentioning
confidence: 72%
“…Despite some of us being reluctant to perform invasive procedures on the very elderly, we are repeatedly provided data supporting more aggressive and invasive care for the very elderly population. Now Ismayl et al have provided us with more of that sort of evidence 1 …”
Section: Years Of Study Mortality With Pci Vs W/o Pci Mortality With ...mentioning
confidence: 99%
“…Now Ismayl et al have provided us with more of that sort of evidence. 1 Ismayl et al report outcomes in nonagenarians admitted with ST-elevation myocardial infarction (STEMI) stratified by whether or not they had a primary percutaneous coronary intervention (pPCI).…”
mentioning
confidence: 99%